Validation of the name Guihaia lancifolia (Arecaceae) - Luo, Kaiwen; Xing, Fuwu; Tian, Jing (Phytotaxa, 2017)
The name Guihaia lancifolia Luo & Xing (2016: 286) was not validly published because more gatherings, K. W. Luo 1509012 (fruit), K. W. Luo 1605035 (flower, ♂) and K. W. Luo 1605036 (flower, ♀), were designated as type (Art. 40.2 of the ICN, McNeill et al. 2012). The name Guihaia lancifolia is validated here by indicating a single gathering, K. W. Luo 1605035 (flower, ♂), as holotype.